Comparison of Two Parameters Models for clay brick masonry confinement (Fracture and Structural Integrity, 2019)
Masonry elements are often strengthened in order to improve their structural capacity. Generalized methods to assess the behavior of confined masonry columns are not available in the technical literature. They have been usually derived from concrete confinement models. However, concrete and masonry present several crucial differences due to their physical and mechanical properties. In fact, generalized models to assess the axial capacity of masonry columns were limited by the strong variability and heterogeneity of physical and mechanical properties. However, the recent scientific researches provided relevant information on the experimental behavior of confined masonry columns. In this paper, a confinement model has been proposed to assess the axial capacity of clay brick masonry strengthened using several strengthening systems. The model has been validated by means of comparisons with experimental results. In order to assess the potential of the proposed model, the comparison was carried out also with other available mechanical models.
Keywords: Mechanical approach; masonry; confinement; experimental tests